RAHASIA TAHAJJUD UNTUK MENINGKATKAN KECERDASAN SPIRITUAL, EMOSIONAL, DAN INTELEKTUAL (Telaah PemikiranYazid al-Bustomi) - Syamsuddin, -; Afroyim, Khunainah (Al Tadib : Jurnal Ilmu Pendidikan, 2017)
Ibn Manzur in Lisanul 'Arob explained, said ھجد الرجل "hajada ar rojulu", which means aperson that sleeps at night. The word متھجد "mutahajjid" are people who wake up from sleep toperform prayers. In summary, understanding Tahajjud prayer is sunnah prayer done by someone afterhe wake up at night even though only briefly short time. If analyzed carefully so it is apparent thattahajjudis very useful to improve the intelligence of the spiritual, emotional, and intellectual.The goal of this study is to give direction to solve the problem as follows: To know the effect oftahajjud in improving spiritual, emotional,and intellectual intelligence.The method used in thisresearch is a kind of library research and also phylosophy research that depart from theories or termswhich are common to the next to the realities specific to get a new conclusion. The result of the study:(1) because tahajjud is worship of the most special then tahajjud done with full sincerity will be ableto resolve the problems in our lives. (2) Tahajjud which is done sincerly, can bring peace of mind aswell as mind therapy. (3) Enhance spiritual intelligence in ESQ 165 initiated by Ary GinanjarAgustian known the term Zero Mind Process (ZMP). (4) prayer tahajjud can also increaseintelligence. This is influenced by the alpha wave that brought us into the subconscious mind duringsleep.Keywords: Tahajjud, spiritual intelligence, emotional intelligence, intellect